Pengukuran Penerimaan Website Mulawarman Online Learning System (MOLS) Pada Universitas Mulawarman Menggunakan Theory Of Planned Behavior (TPB) - Herniyanti Herniyanti; Putut Pamilih Widagdo; Vina Zahrotun Kamila (Mulawarman University, 2023)
One of the information technology services available at Mulawarman University is MOLS (Mulawarman Online Learning System). Implementing the Mulawarman Online Learning System (MOLS) is a strategic action to improve the learning process and interaction between students and lecturers in higher education. The Mulawarman Online Learning System (MOLS) functions as a tool to support learning management and make interaction between students and lecturers easier. The purpose of this study is to see the level of user acceptance of MOLS technology using the Theory of Planned Behavior, where the results of this study can be used for strategic decision making based on research results. Sampling used is all faculties at Mulawarman University and obtained as many as 104 respondents. The data obtained were analyzed using SmartPLS software version 4. Based on the results of data analysis, the following results were obtained: (1) perceived behavioral control had a positive and significant effect on behavior intention, (2) Attitude had no positive and significant effect on behavior intention, (3 ) Subjective Norm has a positive and significant effect on behavior intention and (4) behavior intention has a positive and significant effect on behavior.